TI_GERICHTE 52.2021.270 vom 4. Juni 2021 , Commessa pubblica- Aggiudicazione del servizio di trasporto scolastico - TI Tribunale d'appello (2021)
Commessa pubblica- Aggiudicazione del servizio di trasporto scolastico